Persepsi Konsumen Terhadap Kualitas Pelayanan Make Up Artist Pria - Aulia Nifa, Asya (Jurnal Tata Rias, 2021)
Asya Aulia Nifa, Thesis : Consumer Perception Of Service Quality Of Men's Make Up Artist. Cosmetology Education Study Program, Faculty of Engineering, Jakarta State University. 2021 The desire of women and men to beautify themselves through make-up is very high. The high need for make-up is used as a business opportunity for all circles of society, men and women. One way to determine the quality of a make-up service is to know the service quality of a male make-up artist. The purpose of this study is to find out about consumer perceptions of the service quality of male make up artists. This research is a descriptive quantitative research in collecting data this research uses purposive sampling technique. Sources of data used are primary data sources and secondary data instruments are observations, interviews and documentation. Based on the results of the chi square analysis test on aspects of service quality Asymp. Sig Responsiveness 0,000 < 0.05, Asymp. Guaranteed sig 0,000 < 0.05, Asymp. Empathy sig 0,000 < 0.05, and Asymp. Sig Reliability 0,000 < 0.05. Aspects of service quality that have an influence on consumer perceptions of the service quality of male make up artists are responsiveness, assurance, physical evidence, empathy and reliability.